2011
DOI: 10.1093/abbs/gmr010
|View full text |Cite
|
Sign up to set email alerts
|

Specific targeting of nasopharyngeal carcinoma cell line CNE1 by C225-conjugated ultrasmall superparamagnetic iron oxide particles with magnetic resonance imaging

Abstract: An accurate definition of clinical target volume (CTV) is essential for the application of radiotherapy in nasopharyngeal carcinoma (NPC) treatment. A novel epidermal growth factor receptor (EGFR)-targeting contrast agent (C225-USPIO) was designed by conjugating ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles with cetuximab (C225), to non-invasively define the CTV of tumor. The immunobinding activity of C225-USPIO to NPC cell line CNE1 was confirmed by flow cytometry and immunofluorescence. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A number of nanoparticle systems have been investigated in conjunction with EGFR targeting toward a variety of cancers, including nanoparticles composed of gold [13], iron oxide [14,15], dendrimers [16], high-density lipoprotein [17], L-protein [18], poly(ε-caprolactone) [19], lactic acid–lysine copolymers [20], gelatin [21], human serum albumin [22], heparin [23] and liposomes [24]. …”
mentioning
confidence: 99%
“…A number of nanoparticle systems have been investigated in conjunction with EGFR targeting toward a variety of cancers, including nanoparticles composed of gold [13], iron oxide [14,15], dendrimers [16], high-density lipoprotein [17], L-protein [18], poly(ε-caprolactone) [19], lactic acid–lysine copolymers [20], gelatin [21], human serum albumin [22], heparin [23] and liposomes [24]. …”
mentioning
confidence: 99%
“…Effective targeting of superparamagnetic iron oxide nanoparticles, excellent MRI contrast agents, to cells over-expressing EGFR has been demonstrated (Liu et al 2011; Bouras et al 2012). Liu et al (2011) proposed MRI imaging of cetuximab-conjugated iron oxide nanoparticles for early detection of nasopharyngeal carcinoma as well as for defining the clinical target volume for the application of radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2011) proposed MRI imaging of cetuximab-conjugated iron oxide nanoparticles for early detection of nasopharyngeal carcinoma as well as for defining the clinical target volume for the application of radiotherapy. Similarly, Bouras et al (2012) have shown that cetuximab-conjugated iron oxide nanoparticles can provide MRI contrast enhancement as well as confer radiosensitivity to glioblastoma cell lines in vitro and in vivo tumors.…”
Section: Resultsmentioning
confidence: 99%
“…47 Liu et al also found that C225-USPIO has potential use as an MRI contrast agent to noninvasively detect early-stage nasopharyngeal carcinoma with EGFR overexpression. 48 Furthermore, Shevtsov et al 49 studied SPION conjugated with recombinant human epidermal growth factor (SPION-EGF) as a potential agent for MRI contrast enhancement in malignant brain tumors. They first analyzed the interaction of SPION-EGF conjugates with cells in a C6 glioma cell culture.…”
Section: Using Spion In Cancer Imaging Applicationsmentioning
confidence: 99%